Dual‐frequency DRA‐based MIMO antenna system for wireless access points. Issue 8 (22nd May 2017) - Sharawi, Mohammad S.; Podilchak, Symon K.; Khan, Muhammad U.; Antar, Yahia M.
Abstract : An eight‐element, dual‐frequency, multiple‐input–multiple‐output (MIMO) antenna system is proposed. Cylindrical dielectric resonator antennas (cDRAs) were used as the radiating elements in the MIMO antenna system. One group of four cDRAs covers the 2.45 GHz band, whereas another four cover the second band at 5.8 GHz. A reflector element was also proposed to tilt the radiated beam patterns and reduce field correlations for the MIMO antenna system. The high‐band antenna elements were rotated 45° with respect to their low‐band counterparts, on the antenna ground plan, for compactness and printed circuit board integration such that the complete antenna system occupies a volume of 160 mm×160 mm×14.8 mm. The measured bandwidths (BWs) were at least 90 and 200 MHz for the two bands of operation while the envelope correlation coefficient (ECC) was <0.17. A study of different metallic reflectors was also provided in terms of the impedance matching, isolation, BW, andECC. Specific applications for the proposed design include wireless local area networks and other fourth generation access points.